ANALISIS HUKUM KEABSAHAN PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) - Purba, J.E. Melky (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2023)
The validity of ownership of land rights is often disputed, even to the court. Legal certainty of land registration basically lies in the power of land certificates as proof of land ownership, including evidence in court, if in the future there is a dispute over land ownership rights. Land registration in Indonesia that uses the negative echelon at the empirical level has an impact on the legal certainty of registration and certainty of land certificates as proof of land ownership for certificate holders. This research is descriptive analysis, which leads to empirical juridical. The type of data used in this research is sourced from primary or field research and secondary data obtained from library research consisting of primary, secondary and tertiary legal materials. Data analysis used in the research, namely qualitative data analysis. The validity of certificates through complete systematic land registration can be seen from two aspects, first the validity of formality, namely land certificates issued by authorized institutions. The material validity of land certificates is still relative, because the land registration system adheres to a negative stelsel with a positive tendency. Legal protection for land certificate holders through complete systematic land registration, namely the guarantee of legal certainty for landowners, because land certificates through proof of ownership and as a means of proof in court. Therefore, the land certificate is considered valid and the party listed in the certificate is considered the owner of the land as long as no other party can prove otherwise. Keywords: Legal Analysis, Land Registration, Complete Systematic.